Cognitive Screening Tools for Late Career Physicians: A Critical Review. (May 2021) - Garrett, Kelly Davis; Perry, William; Williams, Betsy; Korinek, Lauri; Bazzo, David E. J.
Screening measures are widely used in medicine to assess the increased probability that members of a defined population have a particular condition and therefore require more extensive assessment. The rationale for prospective screening of late career physicians (LCPs) is drawn from the following circumstances: Senior physicians—prone to the vicissitudes of aging—comprise nearly a third of the US physician workforce, physicians are poor at self-evaluation, data suggest many have clinically relevant cognitive decline, and screening is an evidence-based, method to detect individuals at risk and determine whether a comprehensive evaluation is necessary. A handful of professional organizations (eg, surgeons, obstetricians, and a growing number of medical staff credentialing committees) have developed policies in this arena. This focused review compares cognitive screening methods used or recommended for LCPs, with particular attention to the psychometric properties, ease of operational implementation, and appropriate application to physicians—a population selected for high cognitive reserve and skills. Further, we identify gaps in knowledge and practice, including the need for more career-span normative data on physicians' cognitive and work performance. Stakeholders can improve rehabilitation and other supports to LCPs in transition, calling upon the unique expertise of those neuropsychologists who are trained on conducting fitness for duty evaluations, as well as rehabilitation professionals who can assist in developing modifications to practice when indicated or facilitate graceful transitions to retirement when necessary.